History of the Role of the three Friends Village Unit Cooperative (KUD) in Prospering Oil Palm Farmers in Pulau Village, Batanghari Regency, Jambi Province - Humairah, Lathifah; Zaiyardam, Zaiyardam; Efendi, Harry (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to explain history of the role of the KUD of three Sekawan in the welfare of the palm oil farmer community in the village of Pulau Batanghari Regency, Jambi Province. The role in question is through the KKPA program that partnered with PT Citra Mulia Manunggal during 2012-2023. The methods used in this study are historical scientific methods, including: Heuristics, Source Criticism, Interpretation and Historiography. Based on the results of the research conducted, it is known that the KKPA program that was held by KUD three Sekawan had not been able to encourage the welfare of oil palm farmers in the village of Pulau Batanghari Jambi Regency during 2012-2023. This is because in the implementation of the KKPA, problems were encountered, including: The absence of transparency of fund management and publication distribution of business results carried out by the KUD management to cooperative members. The unclear distribution of results and the period of land surrender to cooperatives as a form of partner cooperation with PT. Citra Mulia is also not in accordance with the agreement. For this reason, further supervision is needed from all parties involved in its implementation.